Omics Technology for the Promotion of Nutraceuticals and Functional Foods - Pandita, Deepu; Pandita, Anu (Frontiers in Physiology, 2022)
The influence of nutrition and environment on human health has been known since ages. Phytonutrients (7,000 Flavonoids and Phenolic Compounds; 600 Carotenoids) and pro-health nutrients-nutraceuticals positively add to human health and may prevent disorders like cancer, diabetes, obesity, cardiovascular diseases and dementia. Plant derived bioactive metabolites have acquired an imperative function in human diet and nutrition. Natural phytochemicals affect the genome expression (Nutrigenomics and Transcriptomics) and signaling pathways and act as epigenetic modulators of epigenome (Nutri Epigenomics). Transcriptomics, Proteomics, Epigenomics, miRNomics and Metabolomics are some of the main platforms of complete omics analyses, finding use in functional food and nutraceuticals. Now the recent advancement in integrated omics approach which is amalgamation of multiple omics platforms is practiced comprehensively to comprehend the food functionality in food science.